EFFECTIVENESS OF EDUCATIONAL MEDIA IN PREVENTING ANEMIA AMONG ADOLESCENT GIRL: A SCOPING REVIEW - Lusiana, Dikta Ayu May; Nugraheni, Sri Achadi; Musthofa, Syamsulhuda Budi (Poltekkes Kemenkes Bandung, 2025)
Anemia is a major public health issue globally, particularly among adolescent girls, with significant impacts on cognitive and psychomotor development. Despite the importance of prevention, anemia remains widespread, especially in developing countries. This study aimed to evaluate the effectiveness of various educational media in preventing anemia among adolescent girls. A scoping review was conducted following the Arksey and O'Malley framework, with articles identified from three major databases: ScienceDirect, PubMed, and Scopus. Out of 2,560 articles, seven studies met the inclusion criteria, focusing on media formats such as animated educational videos, PAKEM (Active, Creative, Effective, and Fun Learning) model, and print materials like booklets and pocketbooks. The findings reveal that interactive digital media, especially animated educational videos, were highly effective in improving adolescents' knowledge, attitudes, and behaviors regarding anemia prevention. These media, with engaging features like dynamic visuals and interactive elements, captured the attention of adolescent girls, facilitating better understanding, and behavior change. The PAKEM model also showed positive results, particularly in increasing adherence to iron supplementation. In contrast, traditional print media, while useful as supplementary tools, were less effective in engaging adolescents compared to digital media. A combined approach using both digital and print media, along with participatory methods such as peer education, was identified as the most effective strategy. These results emphasize the importance of utilizing diverse educational media to enhance anemia prevention efforts and provide valuable insights for developing comprehensive, effective health intervention strategies.